2020
DOI: 10.46542/pe.2020.202.302309
|View full text |Cite
|
Sign up to set email alerts
|

Student and faculty perceptions related to online learning during the COVID-19 pandemic in Indonesia

Abstract: Introduction: This study aimed to explore pharmacy students' and faculty members' perception of online learning at the Faculty of Pharmacy Universitas Andalas. Methods: A survey was administered to 522 undergraduate students, 140 pharmacist professional students, and 51 faculty members via an online electronic survey (Google Forms). Demographic data, online learning experiences, and online learning acceptance of students and faculty members were collected through the survey. Results: Five hundred forty-five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Suddenly, face-to-face universities around the world have been forced to progressively adapt new learning activities and different evaluation methodologies [ 5 , 6 ] derived from distance education [ 7 , 8 , 9 , 10 ] which, in principle, has meant the use of human resources. Furthermore, the impact of this precipitate transition to online education methods in engineering studies is still not fully known [ 11 ], and many challenges related to online education methods are still to be addressed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Suddenly, face-to-face universities around the world have been forced to progressively adapt new learning activities and different evaluation methodologies [ 5 , 6 ] derived from distance education [ 7 , 8 , 9 , 10 ] which, in principle, has meant the use of human resources. Furthermore, the impact of this precipitate transition to online education methods in engineering studies is still not fully known [ 11 ], and many challenges related to online education methods are still to be addressed [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, they agreed that IT department of their university supports their online teaching (56.4%) and constantly upgrading their systems to meet the challenges (30.3%). Indonesian pharmacy teachers also opined that internet connectivity is the main obstacle in online teaching and learning [ 11 ]. The slow internet connectivity results in students’ disengagement during online teaching session [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, survey technique was adopted for the modification and validation of a questionnaire for evaluating the faculty response to online teaching including their perception, attitude and experiences [10][11][12]. Google forms was developed and used to get their response.…”
Section: Methodsmentioning
confidence: 99%
“…Recent and related studies in Indonesia have also highlighted that both teachers and students perceived that online learning could accomplish knowledge learning objectives (LOs), but not in cultivating attitude or skill learning goals, and concluded that online learning is ineffective during the pandemic (Syofyan et al, 2021). While some lecturers and students generally believed that online learning online learning is a viable alternative for performing educational activities, learning activities and media should nevertheless be carefully chosen to ensure that all elements of the LOs are met.…”
Section: Achieving Learning Outcomementioning
confidence: 99%
“…With the gearbox illustration, it is rationalized that the first area (achieving learning outcomes) must be achieved first (Bralić & Divjak, 2018; Mo et al, 2021). Only then can the second and the third gears could move (Syofyan et al, 2021). This is in conjunction with the research gaps indicated above.…”
Section: Introductionmentioning
confidence: 99%